Subsurface ground temperature, Tasiapik Valley Nunavik, Québec : Températures sousterraines, vallée de Tasiapik, Nunavik, Québec - Lemieux, Jean-Michel; Murray, Renaud; Fortier, Richard; Dagenais, Sophie; Fortier, Philippe; Young, Nathan L (Nordicana D, 2020)
This dataset includes subsurface temperature data from four different sample locations within the Tasiapik Valley, near the village of Umiujaq, Nunavik, Quebec, Canada. Each sample location has a different form of land cover. The depth of investigation was 4 meters for the site with lichens and low shrubs (LLS; DL), and 2 meters for the sites with lichens and herbs (LH; DH), medium shrubs (MS; DA) and trees (T; DP). Data were collected from 27 June 2014 – 7 July 2019 using Decagon© 5TM volumetric water content and temperature probes. : Cet ensemble de données comprend des données sur la température du sol pour quatre emplacements différents dans la vallée de Tasiapik, près du village d'Umiujaq, Nunavik, Québec, Canada. Chaque emplacement a une couverture végétale différente. La profondeur maximale d'investigation est de 4 mètres pour le site avec des lichens et des arbustes bas (LLS; DL), et de 2 mètres pour les sites avec des lichens et des herbes (LH; DH), des arbustes moyens (MS; DA) la pessière (T; DP ). Les données ont été collectées du 27 juin 2014 au 7 juillet 2019 à l'aide de sondes de teneur en eau volumétrique et de température Decagon © 5TM.